ESA's Aeolus Mission Reveals Uncertainties in Tropical Wind and Wave‐Driven Circulations - N. Žagar; R. Pilch Kedzierski; G. DeChiara; S. Healy; M. Rennie; F. Sielmann (Geophysical Research Letters)
Abstract The recent European Space Agency Aeolus mission provided global coverage of horizontal line‐of‐sight (HLOS) wind profiles. Using observing system experiments with HLOS winds in the ECMWF data assimilation system, we quantify the effects of HLOS winds on wave circulation and the mean zonal state in the tropical upper troposphere and lower stratosphere (UTLS) in relation to the background shear. Despite large observation random errors, the assimilation of HLOS winds produced substantial effects on Kelvin and n=1 Rossby wave zonal winds, and, through 4D‐Var, on mixed Rossby‐gravity waves. The effects are asymmetric in easterlies and westerlies, consistent with the background shear. The largest analysis differences due to HLOS winds occurred during the 2019/2020 disruption of the quasi‐biennial oscillation. The results highlight the importance of observing shear zones within the UTLS for reducing tropical analysis uncertainties.